Chronic Illness in childhood – empirical research – quantitative research - White, Francesca (2010)
Abstract Aim: The study investigated whether having a child with diabetes impacts on family functioning at mealtimes compared to a comparison group. Background: Dietary recommendations are an important aspect of many paediatric chronic illness treatment regimes (Spieth et al 2001). This is particularly the case for children with Type one Diabetes Mellitus (T1DM). Evidence found that parents of young children with T1DM commonly report mealtimes and adherence to the diabetes dietary recommendations to be among the most difficult component of their child’s care. It is clear from the previous research that some families perceive mealtimes and nutrition management as challenging (Powers et al 2002). However, the studies were conducted in America and it is hard to generalise the findings to the United Kingdom. Method: This study took a quantitative approach by administering a questionnaire, adapted from the About Your Child’s Eating Revised (AYCE-R) by Davies et al (1993) with additional questions about family eating habits and the possible cause of mealtime concern. Parents were approached to participate in this study over a 3 month period at a paediatric diabetes clinic (diabetes group) and endocrine clinic (comparison group) in a large teaching hospital in the East Midlands.